America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

La médiation au service des familles recomposées - Gaudreau, Louise (Service aux collectivités de l'UQAM/Protocole Relais-femmes, 1995)
Ce document porte sur l'expérimentation et l'évaluation du programme de formation en médiation familiale. Il présente la méthodologie suivie pour la conception du programme, les résultats et enfin quelques recommandations à l'égard de celui-ci. Il fournit aussi une définition de la famille recomposée et de la médiation communautaire familiale, avant d'aborder des thèmes tels que la situation des femmes, la relation d'aide, l'intervention d'aide en médiation, la résolution de problèmes, etc.
Keywords: 1900-1999; 1990-1999; SAC; amériques; famille; famille recomposée; incomplet; périodes historiques; québec; rapport; recherche partenariale; régions géographiques; thématiques

Identités en devenir et famille subvertie dans l'oeuvre de Jovette Marchessault - Poirier, Martin (Université du Québec à Montréal, 1995)
Ce mémoire présente une analyse du roman Des cailloux blancs pour les forêts obscures (Montréal: Leméac, 1987) de Jovette Marchessault. L'approche théorique utilisée est avant tout inspirée du travail de Marianne Hirsch (The Mother/Daughter Plot, 1989) qui revoit la notion de «roman familial» de Freud d'un point de vue féministe. Les réflexions de Luce Irigaray et de Claire Lejeune à propos de la notion identitaire et de la constitution de famille servent également à l'analyse. La question principale qui guide l'ensemble des quatre chapitres du mémoire est la suivante: en quoi les remises en question identitaires des personnages féminins et masculins arrivent-elles à transformer les structures de la famille patriarcale et les caractéristiques du roman familial traditionnel?
Keywords: amériques; approches et analyses; arts; discipline; famille; mémoires/thèses; patriarcat; québec; régions géographiques; systèmes d'oppressions; thématiques; études littéraires